Projecting marine species range shifts from only temperature can mask climate vulnerability. (27th September 2019) - McHenry, Jennifer; Welch, Heather; Lester, Sarah E.; Saba, Vincent
Abstract: Climate change is causing range shifts in many marine species, with implications for biodiversity and fisheries. Previous research has mainly focused on how species' ranges will respond to changing ocean temperatures, without accounting for other environmental covariates that could affect future distribution patterns. Here, we integrate habitat suitability modeling approaches, a high‐resolution global climate model projection, and detailed fishery‐independent and ‐dependent faunal datasets from one of the most extensively monitored marine ecosystems—the U.S. Northeast Shelf. We project the responses of 125 species in this region to climate‐driven changes in multiple oceanographic factors (e.g., ocean temperature, salinity, sea surface height) and seabed characteristics (i.e., rugosity and depth). Comparing model outputs based on ocean temperature and seabed characteristics to those that also incorporated salinity and sea surface height (proxies for primary productivity and ocean circulation features), we explored how an emphasis on ocean temperature in projecting species' range shifts can impact assessments of species' climate vulnerability. We found that multifactor habitat suitability models performed better in explaining and predicting species historical distribution patterns than temperature‐based models. We also found that multifactor models provided more concerning assessments of species' future distribution patterns than temperature‐based models, projecting that species' ranges will largely shift northward and become more contracted and fragmented over time. Our results suggest that using ocean temperature as a primary determinant of range shifts can significantly alter projections, masking species' climate vulnerability, and potentially forestalling proactive management. Abstract : Climate change research predicting marine species' range shifts has mainly focused on expected responses to changing ocean temperatures, overlooking how other environmental covariates could affect future distribution patterns. We explore how this emphasis on ocean temperature could impact species' climate vulnerability assessments, comparing outputs from temperature‐based habitat suitability models to those that include multiple environmental covariates. We find that multifactor models perform better in explaining and predicting species' historical distribution patterns. These models also make more concerning projections for species' future distribution patterns, that is, that species' ranges will largely shift northward and become more contracted and fragmented over time.